On the relevance of economic preferences, values, norms, and socio-demographics for electricity consumption - Elke D. Groh; Andreas Ziegler (ZBW - Leibniz Information Centre for Economics, 2020)
As long as electricity is generated from fossil fuels, the reduction of its consumption is an important direction for climate protection and related policy measures. Based on data of more than 3700 respondents in Germany, we thus empirically examine the relevance of a large set of well-known determinants of electricity consumption such as household and dwelling char-acteristics, but also of individual values and norms. Since behavioral economics highlights the importance of economic preferences in such public good contexts, we additionally consider risk and time preferences, trust, altruism, and reciprocity in our econometric analysis. With respect to the latter group of factors, however, only time preferences have a strong significant effect on electricity consumption. Furthermore, norms also play only a minor role. In contrast, our estimation results suggest a high relevance of dwelling characteristics and socio-demographics. Interestingly, it seems that a low electricity consumption is no important cli-mate protection activity of German inhabitants with strong environmental values, which is in contrast to the demand of such citizens for green electricity.
Keywords: Q41; Q54; 330; electricity consumption; economic preferences; individual values; social norms; econometric analysis